The Legitimacy of Implementing The Concept of Sustainable Development In The Motorsports Industry As Assessed By Formula 1 Fans: A Quantitative Research - Dorota TENETA; Karol GAJDA (Communications of International Proceedings, 2025)
For the purposes of this study, a survey was conducted with the main objective of assessing the level of awareness and acceptance of the idea of sustainable development among Formula 1 fans in the context of the motorsports industry. A survey was used as the research method. The survey was conducted from January to February 2025 among F1 racing fans, using a questionnaire embedded in Microsoft Forms. It was sent to members of a group created on Facebook, bringing together Polish F1 fans. A total of 296 people took part in the survey. The synthesis of qualitative material obtained through open-ended questions was conducted using content analysis and semantic clustering. The survey shows that more than half of the respondents declared their familiarity with the concept of sustainable development. It was most often defined in accordance with the classic approach proposed in the Brundtland Report. The degree of acceptance of ESG activities varied. More than half of the respondents denied the sense of the motorsport industry's involvement in Governance. As for “Social” and “Environmental,” the shares of negative votes were 46% and 34%, respectively.
Keywords: motorsport industry; Formula 1; sustainable development/ ESG; F1 fans